Still more about history than about the present – picture of Russia, Germany and Ukraine in the Polish media in the second half of 2013 (Economic and Political Thought, 2017)
The paper aims to present the image of Poland’s neighbours, namely:Russia, Ukraine and Germany, presented in the Polish media between Julyand December 2013. To obtain a possibly complete final image, a databaseof textual news articles was created, and its content was gathered from manyvarious on-line sources, chosen due to their popularity and wide spectrumof political views. The preliminary dataset consisted of 8096 articles. Theanalysis of the final dataset was conducted by applying a mixed-methodmethodology, employing CAQDAS (QDA Data Miner and Wordstat).The results of the analysis showed that all the Polish media were focusedmainly on neighbouring countries and tended to depict them in rather darkcolours; moreover, a surprisingly large share of statements mentioningGermany, Russia and Ukraine were focused on historical issues, mainly ofthe Second World War period. The results of the research lead to emergenceof new research hypotheses: to what extent the image of foreign countrieswas a reflection of social moods in 2013 and an indicator of the upcomingparliamentary and presidential election results? Was it mainly a product ofthe publishers aiming to influence the readers’ political choices? Regardlessof which of the above hypotheses is true, it can be assumed that the mediaimage could be applied in the prediction and analysis of international relationsstrategies employed in particular countries. Evidence for the reasonablenessof this hypothesis is provided by the analysis of the current priorities of publicdiplomacy in Poland.